An Improved Rule-Based Energy Management System: Effective Solution to Achieve Collaborative Control of Batteries in Multi-Prosumers Community Microgrid - Jiawei Huang; Chengxiong Mao; Bin Liu; Dan Wang; Rui Gao; Bo Gu (IEEE Access)
The integration of renewable energy sources into community microgrids is increasingly critical for reducing reliance on utility grids and promoting local energy consumption. In this paper, an improved rule-based energy management system (EMS) for the community microgrid is proposed, which optimizes energy scheduling to enable the system to achieve real-time supply-demand balance in both the grid-connected mode and the off-grid mode. To realize the proposed EMS function, an improved peer-to-peer fast settlement transaction mode is proposed, which is suitable for both the grid-connected mode and the off-grid mode, and fuzzy control is employed to manage complex real-time control problems. Additionally, a non-communication internal price transmission mechanism is proposed to ensure the EMS operates effectively even under harsh communication conditions. Simulation results show that the proposed EMS can rapidly respond to supply-demand variations, maintaining near self-sufficiency in both the grid-connected and the off-grid mode. Specifically, the EMS achieves at least a 55% reduction in the net exchange power deviation from zero and the supply-demand ratio (SDR) deviation from the target level of 1 compared to the rule-based EMS used for comparison. Overall, the proposed EMS demonstrates excellent real-time performance, robustness, and immunity to communication issues.